Supervisors' Support for Nurses' Meal Breaks and Mental Health. (March 2015) - Hurtado, David A.; Nelson, Candace C.; Hashimoto, Dean; Sorensen, Glorian
Meal breaks promote occupational health and safety; however, less is known about supervisors' support for nurses' meal breaks. In this study, the researchers tested whether the frequency of meal breaks was positively related to supervisors' support of nurses' meal breaks, and whether more frequent meal breaks were associated with less psychological distress. This study is based on a cross-sectional survey of 1, 595 hospital nurses working on 85 units supervised by nursing directors. Specific meal-break support was measured at the nursing director level; frequency of meal breaks and psychological distress were measured at the individual nurse level. Multilevel adjusted models showed a positive association between supervisors' support for meal breaks and the frequency of nurses' meal breaks (β = .16, p < .001). Moreover, nurses who took meal breaks more frequently reported lower psychological distress (β = −.09, p < .05). Meal breaks might be daily opportunities to promote mental health and fatigue recovery and provide downtime.